A tool for investigating systematic bias in BOLD based MRI methods: An implementation of the detailed BOLD signal model - Blockley, N; Griffeth, V (University of Oxford, 2015)
The following code was developed using MATLAB R2014b during 2014 in order to investigate sources of systematic bias in calibrated BOLD functional MRI (fMRI) based mapping of the oxygen extraction fraction. However, this tool may be useful for improving our understanding of other BOLD based fMRI methods.